Ritual and religious experience in early christianities: the spirit in between - McCollough, David John (Wissenschaftliche Untersuchungen zum Neuen Testament, 2022)
In diesem Band stellt David John McCollough die weit verbreiteten Annahmen in Frage, dass Paulus dachte, der Geist werde durch die Wassertaufe vermittelt, dass „Rechtfertigung“ nicht auf Erlebnissen beruhe und nichts mit Ritualen zu tun habe, dass Lukas inkohärent oder ein schlechter Redakteur gewesen sei und dass die Wassertaufe der wichtigste Initiationsritus der frühen Christenheit gewesen sei.Inhaltsübersicht1. Introduction 2. Exegetical Methodology2.1 Introduction2.2 Acts: The Dual Problems of Historicity and Intelligibility2.3 Methodological Problems2.4 Methodological Solutions2.5 Acts and History Again: Which Historical Audience? 3. Exegesis3.1 Pauline Epistles3.2 Luke-Acts 4. Interpretation4.1 Introduction4.2 Understanding Notions of Culture and Their Relationship to Spirit Possession4.3 What’s So Special About Initiation? Ritual Form Theory and Lukan Baptism(s)4.4 Spirit Impartation as Performative Ritual4.5 Commitment Signalling Theory: Costly and Charismatic4.6 Identity Fusion in the Early Christian Sect: How Initiatory Spirit-Possession Formed Social Bonds Among the Early Christians4.7 Sacred Values and the Early Christian Sect4.8 Emotion and the Early Christian Sect4.9 Mediation in the Early Christian Sect4.10 Why Did People Become Christians in the First Century? 5. Conclusion